Djibouti : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2009)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for Djibouti. Djibouti's National Initiative for Social Development ('Initiative Nationale pour le Developpement Social'-INDS) provides a comprehensive vision for economic growth and poverty reduction. Notwithstanding some important achievements of the PRSP-I, overall progress in achieving its objectives has been limited. IMF staff commends the government for a well-designed and ambitious poverty reduction strategy. IMF staff considers that the INDS benefits from better prioritization and draws lessons from the shortcomings in the implementation of the PRSP-I.